Impact Of Physical Independence On Participation Restriction In Individuals With Spinal Cord Injury - Mahaveer, Navami; K B, Komal; Fernandes, Alisha; Jain, Mahaveer (Journal of Neonatal Surgery, 2025)
Traumatic Spinal Cord Injury (SCI) is a critical condition that significantly impacts an individual’s physical functioning, social participation, and overall quality of life. Individuals with SCI often encounter numerous challenges in reintegrating into the community, primarily due to participation restrictions stemming from reduced physical independence. Understanding the barriers and facilitators that influence physical independence is essential for enhancing rehabilitation outcomes and community involvement. This cross-sectional study aimed to explore factors influencing physical independence-related participation restrictions among individuals with SCI. Data were collected from 30 individuals with traumatic SCI through face- to-face interviews using the CHART-SF questionnaire, administered in the local vernacular language, across KLE Hubli Co-operative Hospital and nearby rehabilitation centers in Hubballi, Karnataka. The responses were scored following CHART-SF guidelines, and descriptive statistics, including mean, median, and standard deviation, were calculated using SPSS version 26.0. The median score in the Physical Independence domain indicated a severe handicap (score of 14), with a significance level set at p ≤ 0.05. The findings underscore the pressing need for targeted rehabilitation and awareness programs, focusing on improving physical independence and thereby enhancing the quality of life for individuals with SCI in and around the Hubballi region